Analysis of Physics Problem-Solving Strategy on Elasticity and Hooke's Law Concepts - Mardian, Vivi; Suwarma, Irma Rahma; Utama, Judhistira Aria (Universitas Negeri Padang, 2023)
roblem solving strategies are needed by students to master physics concepts. Students who are skilled at solving problems can apply physics concepts in the real world. This research aims to analyze students' abilities in solving problems on the concept of elasticity and Hooke's Law. The research method used is a quantitative method. The steps in this research include: determining the topic, finding instruments, collecting data, analyzing data, and interpreting data. This research was distributed to 64 (31.25% male: 68.75% female) high school students. The research instrument is 5 essay questions on elasticity and Hooke's law. The data collection technique is purposive sampling with the criteria that students have studied elasticity material and Hooke's Law and students are taught by the same teacher. Assessment indicators are understanding the problem, writing the problem in terms, planning a solution, solving the problem according to plan, and interpreting and evaluating the solution. Mastery of physics problem solving strategies by high school students has not been achieved optimally. Students were also able to understand the problem with a percentage of 61.6%. The percentages of plan a solution, execute the plan, and evaluate the solution indicators are 49.1%, 45.7%, and 44.3% respectively. Students are skilled in explaining problems in the form of physics terms. It is hoped that future research will be able to develop media that can improve students' abilities in solving physics problems.